Recombinant Human Thyrotropin-Aided Radioiodine Therapy in Tracheal Obstruction by an Invading Well-Differentiated Thyroid Carcinoma - Nickolaos Pontikides; Spyridon Karras; Antonios Papagiannis; Athina Kaprara; Panagiotis Anagnostis; George Noussios; Argyrios Doumas; Apostolos Goropoulos; Ioannis Iakovou; Georgios Kotronis; Konstantinos Bantis; Gerasimos Krassas (Case Reports in Otolaryngology)
Papillary thyroid carcinomas (PTCs) usually extend to lymph nodes in the neck and mediastinum. Rarely, they invade the neighboring upper airway anatomical structures. We report a 56-year-old woman who presented with symptoms of upper airway obstruction. Imaging studies revealed a lesion derived from the thyroid which invaded and obstructed the trachea, which appeared to be a highly differentiated PTC. Total thyroidectomy was performed, with removal of the endotracheal part of the mass along with the corresponding anterior tracheal rings. Two months later, a whole body I131 scan after recombinant human thyroid-stimulating hormone (rh-TSH) administration was performed and revealed a residual mass in upper left thyroid lobe. Subsequently, 150 mCi I131 were given following rh-TSH administration. Nine months later, there was no sign of residual tumor. This case is the first one reported in the literature regarding rh-TSH administration prior to RAI ablation in a PTC obstructing the trachea.